A geometry problem by Christopher Boo

Geometry Level 4

A circle x 2 + y 2 2 x + 4 y 4 = 0 x^2+y^2-2x+4y-4=0 intercepts line y = x + b y=x+b at point A A and B B . Given that a circle has A B AB as its diameter and it passes through the origin, what is the sum of all possible value of b b ?


The answer is -3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Abhishek Sharma
Apr 5, 2015

Circle x 2 + y 2 2 x + 4 y 4 = 0 \large { x }^{ 2 }+{ y }^{ 2 }-2x+4y-4=0 is intercepted by y = x + b y=x+b or y x b = 1 \large \frac { y-x }{ b } =1

We manipulate the equation and write it as x 2 + y 2 2 x ( 1 ) + 4 y ( 1 ) 4 ( 1 ) 2 = 0 \large { x }^{ 2 }+{ y }^{ 2 }-2x(1)+4y(1)-4{ (1) }^{ 2 }=0 .

Now we homogenise equation of circle with the line y x b = 1 \large \frac { y-x }{ b } =1 x 2 + y 2 2 x ( y x b ) + 4 y ( y x b ) 4 ( y x b ) 2 = 0 \large { x }^{ 2 }+{ y }^{ 2 }-2x(\frac { y-x }{ b } )+4y(\frac { y-x }{ b } )-4{ (\frac { y-x }{ b } ) }^{ 2 }=0

The equation that we have got is equation of pair of straight lines passing through the points of intersection of the circle and the line and the origin.

It is given that circle with A B AB as diameter passes through origin, this means O A OA and O B OB are perpendicular to each other ( O O is the origin). Proof of this statement is trivial and is left as a proof to the reader.

As they are perpendicular, coefficient of x 2 {x}^{2} +coefficient of y 2 {y}^{2} =0.

1 + 1 + 2 b + 4 b 4 b 2 4 b 2 = 0 \large 1+1+\frac { 2 }{ b } +\frac { 4 }{ b } -\frac { 4 }{ { b }^{ 2 } } -\frac { 4 }{ { b }^{ 2 } } =0

b = 1 b=1 or b = 4 b=-4 .

3 \large \boxed {-3}

Click here for more details on homogenisation.

Nitish Joshi
Feb 26, 2016

The family of circles passing through the intersection of given circle and line can be represented by

x 2 + y 2 2 x + 4 y 4 + λ ( x y + b ) = 0 x^2+y^2-2x+4y-4+\lambda(x-y+b)=0

where λ \lambda is a parameter.

As the new circle has A B AB as its diameter, the centre of the circle ( 1 λ 2 , λ 2 2 ) \left(1-\dfrac{\lambda}{2}, \dfrac{\lambda}{2} -2\right) must lie on A B AB . So,

λ 2 2 = 1 λ 2 + b \dfrac{\lambda}{2}-2=1-\dfrac{\lambda}{2}+b

Or λ = 3 + b \lambda=3+b

Also since the circle passes through the origin, the constant term must be zero.

So, λ b = 4 \lambda\cdot b=4

Solving the two equations we get b 2 + 3 b 4 = 0 b^2+3b-4=0

Therefore the sum of possible values of b b is 3 -3

Morgan Blake
Apr 2, 2015

Note that the equation of the circle can be rewritten as: ( x 1 ) 2 + ( y + 2 ) 2 = 3 2 (x-1)^2+(y+2)^2=3^2 So, the circle is centred at ( 1 , 2 ) (1,-2) .

Saying that AB is the diameter of the circle is equivalent to saying that AB passes through the centre of the circle. i.e. The line y = x + b y=x+b passes through ( 1 , 2 ) (1,-2) .

This happens only when b = 3 b=-3 .

I think you got the problem wrong. A B AB is the diameter of a new circle.

Christopher Boo - 6 years, 2 months ago

Haha this is funny I too got the problem wrong but by luck got the right answer. cheers :)

neelesh vij - 5 years, 3 months ago

hey! we both got the problem wrong

Aakash Khandelwal - 5 years, 10 months ago
Christopher Boo
Apr 2, 2015

Let the three points be O ( 0 , 0 ) O(0,0) , A ( x 1 , y 1 ) A(x_1,y_1) , B ( x 2 , y 2 ) B(x_2,y_2) .

Since A B AB is the diameter of the new circle, then A O B AOB is a right triangle.

A B 2 = A O 2 + O B 2 ( x 1 x 2 ) 2 + ( y 1 y 2 ) 2 = x 1 2 + y 1 2 + x 2 2 + y 2 2 x 1 x 2 + y 1 y 2 = 0 \begin{aligned} AB^2 &= AO^2+OB^2 \\\\ (x_1-x_2)^2+(y_1-y_2)^2 &= x_1^2+y_1^2+x_2^2+y_2^2 \\\\ x_1x_2+y_1y_2 &= 0 \end{aligned}

This gave us an idea to try to solve for P O R POR .

f ( n ) = { x 2 + y 2 2 x + 4 y 4 = 0 x y + b = 0 f(n) = \left\{ \begin{array}{l l} x^2+y^2-2x+4y-4 = 0 \\ x-y+b=0 \end{array} \right.

Substitute x = y b x=y-b into the first equation,

( y b ) 2 + y 2 2 ( y b ) + 4 y 4 = 0 2 y 2 + ( 2 2 b ) y + ( b 2 + 2 b 4 ) = 0 \begin{aligned} (y-b)^2+y^2-2(y-b)+4y-4 &= 0 \\\\ 2y^2+(2-2b)y+(b^2+2b-4) &= 0 \end{aligned}

Hence,

y 1 + y 2 = b 1 y 1 y 2 = 1 2 ( b 2 + 2 b 4 ) \begin{aligned} y_1+y_2 &= b-1 \\\\ y_1y_2 &= \frac{1}{2}(b^2+2b-4) \end{aligned}

Substitute y = x + b y=x+b into the two equation,

x 1 + x 2 = ( b + 1 ) x 1 x 2 = 1 2 b 2 + 2 b 2 \begin{aligned} x_1+x_2&=-(b+1) \\\\ x_1x_2 &= \frac{1}{2}b^2+2b-2 \end{aligned}

Substitute x 1 x 2 x_1x_2 and y 1 y 2 y_1y_2 into the very first equation,

x 1 x 2 + y 1 y 2 = 0 1 2 b 2 + 2 b 2 + 1 2 ( b 2 + 2 b 4 ) = 0 b 2 + 3 b 4 = 0 \begin{aligned} x_1 x_2+y_1 y_2 &= 0 \\\\ \frac{1}{2} b^2+2b-2 +\frac{1}{2}(b^2+2b-4) &= 0 \\\\ b^2+3b-4 &=0 \end{aligned}

Sum of roots b b is 4 + 1 = 3 -4+1=-3 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...